Enhancing procedural fairness: a critique of the open and inclusive approach to health financing decisions - John Kinuthia (Health Economics, Policy and Law)
This article is a critique of a report, Open and Inclusive: Fair Processes for Financing Universal Health Coverage. The report proposes a framework that is meant to improve procedural fairness and how decisions in financing of health care can be fairer. The author of this article argues that while procedural fairness and the proposed framework are an important step in improving equity in health sector financing, the report falls short on several aspects of achieving the set objectives. First, the report does not place emphasis on the role of civic education as an important component of public education building on access to information. Therefore, there should be caution in assuming that improved dissemination of information will lead to increased civic action. Secondly, the author proposes that the report include principles that should guide how decisions are made in public deliberations when consensus cannot be achieved. Lastly, the framework in the report does not speak to the complexity of the trade-offs that have to be made between health and other sectors. The author argues that a key area of deliberations in health financing is understanding how practitioners in the sector can argue for better funding against other competing sector such as education and agriculture while still finding complementarities.